Adenovirus-Vectored Capsid Proteins of the Serotype A Foot-and-Mouth Disease Virus Protect Guinea Pigs Against Challenge - Xie, Yinli; Chang, Huiyun; Li, Zhiyong; Zhang, Yanming (Frontiers in Microbiology, 2020)
Type A foot-and-mouth disease virus (FMDV) has been detected on China’s pig farms since 2015, and all suspected samples have been strain A/GDMM/CHA/2013. To overcome the shortcomings of inactive FMDV vaccines, we expressed the capsid protein precursor P1-2A and mutated viral 3C protease of FMDV strain A/GDMM/CHA/2013 in a replication-deficient human adenovirus type 5 vector in this study. A significant humoral immune response, T-cell-mediated antiviral response, and mucosa-mediated antiviral response were induced by the adenovirus-vectored FMDV vaccines in BALB/c mice. Immunization of guinea pigs with the adenovirus-vectored FMD vaccines induced significant neutralizing antibodies and anti-FMDV immunoglobulin A antibodies. The recombinant adenovirus rAdv-P12A3CG38SF48S-GD protected 100% of guinea pigs against challenge when administered intramuscularly. Our study demonstrated the potential utility of rAdv-P12A3CG38SF48S-GD as a vaccine against type A FMDV.